The Swiss black swan bad scenario: Is Switzerland another casualty of the Eurozone crisis? - Sebastien Lleo; William T. Ziemba (International Journal of Financial Studies, 2015)
Financial disasters to hedge funds, bank trading departments and individual speculative traders and investors seem to always occur because of non-diversification in all possible scenarios, being overbet and being hit by a bad scenario. Black swans are the worst type of bad scenario: unexpected and extreme. The Swiss National Bank decision on 15 January 2015 to abandon the 1.20 peg against the Euro was a tremendous blow for many Swiss exporters, but also Swiss and international investors, hedge funds, global macro funds, banks, as well as the Swiss central bank. In this paper, we discuss the causes for this action, the money losers and the few winners, what it means for Switzerland, Europe and the rest of the world, what kinds of trades were lost and how they have been prevented.
Keywords: B41; C12; C52; G01; G11; 330; Swiss franc; Euro peg; black swans; currency trading losses; Swiss exports; quantitative easing; negative interest rates